Inferno a novel - Brown, Dan 1964- (Anchor Books, 2014)
In the heart of Italy, Harvard professor of symbology Robert Langdon is drawn into a harrowing world centered on one of history's most enduring and mysterious literary masterpieces--Dante's "Inferno"--as he battles a chilling adversary and grapples with an ingenious riddle--Source other than Library of Congress.